Discursive framing in policies for restricting the marketing of food and non-alcoholic beverages. (May 2022) - Ngqangashe, Y.; Cullerton, K.; Phulkerd, S.; Huckel Schneider, C.; Thow, A.M.; Friel, S.
Highlights: The policies are framed in ways that resonate with neoliberalism and nutritionism. The framing of Policy objectives, terms and standards used to set policy parameters vary depending on the type of policy. Only two policies consider the levels of processing in objectives, terms and standards used to set policy parameters. Abstract: The development of food policies involves many policy actors who use various discursive strategies such as framing problems and policy solutions to align them with their interests. This study aimed to examine the frames and underlying discourses that shape policies for regulating unhealthy food and beverages marketing. Forty-one government and industry policy documents were assessed for the frames and discourses focusing on policy objectives, policy terms and standards used to set policy parameters. Our analysis identified frames that resonate with five paradigms: neoliberalism, nutritionism, public health, vulnerability and levels of processing. These transpire differently across industry versus government policies and different types of food marketing policies (communication/broadcasting policies versus nutrition/public health policies). Government policies emphasize consumer and public health protection while industry policies have a strong theme of commodification and reiterate common industry rhetoric such as personal responsibility. Nutrient profiles are the main standard used to set policy parameters in both industry and government policies. Only one of the 41 policies considers levels of processing and uses the NOVA classification to set policy standards. This analysis expands the understanding of framing that occurs during policy development and how different actor interests are advanced through these frames. Further research is needed to examine how these frames influence policy implementation.